2000
DOI: 10.1159/000025712
|View full text |Cite
|
Sign up to set email alerts
|

Neural Endothelin in Hypertension: Increased Expression in Ganglia and Nerves to Cerebral Arteries of the Spontaneously Hypertensive Rat

Abstract: Endothelin has previously been localised in perivascular nerves of the rat basilar artery. Considering its potent vasoconstrictor and mitogenic properties on vascular smooth muscle, the potential role of a neural source of this peptide in hypertension has been investigated. The trigeminal, superior cervical and sphenopalatine ganglia of Wistar Kyoto (WKY) rats and spontaneously hypertensive rats (SHR) at 16 weeks of age have been examined for immunolocalisation of endothelin at the light and electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…In contrast, in the superior cervical ganglia of spontaneously hypertensive rats, there is an increased intracellular ET-1 immunoreactivity and mRNA. 25 This may reflect different ganglia and/or different hypertensive models. ET-1 can be released from the cultured sympathetic neurons 7 analogous to endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the superior cervical ganglia of spontaneously hypertensive rats, there is an increased intracellular ET-1 immunoreactivity and mRNA. 25 This may reflect different ganglia and/or different hypertensive models. ET-1 can be released from the cultured sympathetic neurons 7 analogous to endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 has previously been demonstrated in the cerebral vascular bed of mammals including rat, rabbit and man, where it was mainly localised to cerebrovascular endothelial cells (Loesch et al 1993, Gorelova et al 1996, Loesch & Burnstock 1996a, b, 1998, Shochina et al 1997. ET-1 has also been shown in cerebrovascular autonomic nerves to large cerebral arteries of rat and man , Milner et al 2000a, Loesch & Burnstock 2002, Loesch 2003. Studies on sensory and sympathetic denervation of the rat suggested that sensory autonomic nerves projecting from the trigeminal ganglion are a more likely source of ET-1-containing perivascular nerves in cerebral arteries than sympathetic nerves from the superior cervical ganglion (Milner et al 2000b).…”
Section: Introductionmentioning
confidence: 94%
“…ET was reported to be present in the basilar artery of the rat [58,59] and post mortem, in human cerebrovascular nerves of the middle cerebral artery [60]. Immunoreactive ET-1 was also detected in endothelial cells of the intima, vascular smooth muscle cells and macrophages of the media and neointima, and in perivascular nerves (axons) varicosities at the boundary between media and adventitia of the middle cerebral artery in a patient with multiple system atrophy with autonomic deficiency [61].…”
Section: Endothelinmentioning
confidence: 99%